Modeling of carbon nanotubes (CNTs) and usage in drug delivery - Esfanjani, Mina; Guyo, Issack Shama (Technium BioChemMed, 2022)
One goal of device science is miniaturization; hence nanotechnology has received Considerable attention. The possibility that the unique properties of nanostructures will result in novel applications and devices is an enticing goal. Carbon nanotubes are allotropes of carbon with a cylindrical nanostructure. Nanotubes have been constructed with a length-to-diameter ratio of up to 28,000,000:1. Potential applications for carbon nanotubes (CNTs) include their use in atomic force microscopy and in adhesives, certainly chemical or mathematical investigation of nanotubes is very important but investigates both of them together has vital notability. there is considerable open literature related to the mathematical modeling of nanotubes, also many authors have investigated the chemical aspects of nanotubes. At the present, in this review, my aim is to both mathematical and chemical aspects of structured, characteristics are investigated.